2004
DOI: 10.1007/s00181-003-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Causality tests of the relationship between the twin deficits

Abstract: We re-examine the causality between the twin deficits by testing for Granger non-causality between BD and CAD based on extended causality tests initially developed by Toda and Yamamoto (1995). Using international data from a sample of twenty developed and developing countries, we find evidence of causality (unidirectional or bi-directional) between the twin deficits for some developing countries. However, the results for developed countries are less persuasive. The empirical findings of this study are robust t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 23 publications
4
38
0
5
Order By: Relevance
“…Particularly, we emphasise that the relationships between the two deficits is subject to evolve depending on dynamics of the economy and due to the impact of various macroeconomic developments. To that end, use of alternative specifications and methods such as use of vector auto regressive models and impulse response functions (for example: Abell, 1990;Anoruo and Ramchandar, 1998), incorporating structural breaks (for example: Hatemi-J and Shukur, 2002;Baharumshah and Lau, 2007), estimating Granger non-causality tests (for example: Kouassi et al, 2004;Pahlavani and Saleh, 2009), multi-integration models (Leachman and Francis, 2002) and co-integration models with regime shifts (for example: Daly and Siddiki, 2009) would help to deepen our understanding of twin deficits and hence, to formulate appropriate macroeconomic policies in Sri Lanka. Such complex specifications as well as general equilibrium model based research is left for future discourse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, we emphasise that the relationships between the two deficits is subject to evolve depending on dynamics of the economy and due to the impact of various macroeconomic developments. To that end, use of alternative specifications and methods such as use of vector auto regressive models and impulse response functions (for example: Abell, 1990;Anoruo and Ramchandar, 1998), incorporating structural breaks (for example: Hatemi-J and Shukur, 2002;Baharumshah and Lau, 2007), estimating Granger non-causality tests (for example: Kouassi et al, 2004;Pahlavani and Saleh, 2009), multi-integration models (Leachman and Francis, 2002) and co-integration models with regime shifts (for example: Daly and Siddiki, 2009) would help to deepen our understanding of twin deficits and hence, to formulate appropriate macroeconomic policies in Sri Lanka. Such complex specifications as well as general equilibrium model based research is left for future discourse.…”
Section: Resultsmentioning
confidence: 99%
“…The appreciation of domestic currency will make exports less attractive and imports more attractive, subsequently worsening the trade balance, which is the major component in the current account deficit. Hence, the Keynesian absorption theory suggests that an increase in budget deficit would induce domestic absorption and import expansion causing an increase or worsening in current account (Kouassi, Mougoue´ and Kymn, 2004). As per these theoretical arguments, the Keynesian proposition can be summarised as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on current account deficits and budget deficits have obtained a variety of results. Prover findings to traditional opinion have been obtained in numerous studies (Bernheim, 1988;Zietz and Pemberton, 1990;Biswas et al, 1992;Rosensweig and Tallman, 1993;Dibooglu, 1997;Egwaikhide, 1999;Khalid and Guan, 1999;Vamvoukas, 1999;Piersanti, 2000;Kulkarni and Erickson, 2001;Leachman and Francis, 2002;Fidrmuc, 2003;Kouassi et al, 2004;Pattichis, 2004;Corsetti and Müller, 2006;Salvatore, 2006;Mukhtar et al, 2007;Lau and Tang, 2009;Ito, 2009;Ganchev, 2010;Holmes, 2011;Iram et al, 2011;Zamanzadeh and Mehrara, 2011;Kalou and Paleologou, 2012;Trachanas and Katrakilidis, 2013). These studies have emphasized that budget deficits have a major impact on current account deficits.…”
Section: Literature Review and Theorymentioning
confidence: 90%
“…Using international data from a sample of twenty developed and developing countries Kouassi et al ( 2004) found either unidirectional or bidirectional evidence between the twin deficits for some developing countries. However, the results for developed countries are less convincing.…”
Section: Literature Reviewmentioning
confidence: 99%